Methodology and First Results of an R&D Road Map for Façade-integrated Solar Thermal Systems. (May 2015) - Maurer, Christoph; Cappel, Christoph; Kuhn, Tilmann E.
Abstract: Within the Aktifas project, a road map is being developed for research and development of façade-integrated solar thermal systems. The road map is based on an analysis of the barriers for façade-integrated solar thermal systems as well as a market overview of existing components. This paper presents the methodology for creating the road map as well as first results. The final road map will be published onhttp://bit.ly/Z0hkso at the beginning of 2015.